The Role of Developing Arabic Language Teachers to Improve Pedagogical Competence in Learning - Buska, Wahyudi; Prihartini, Yogia (Arabiyatuna: Jurnal Bahasa Arab, 2025)
The purpose of this study is to provide insight into how Arabic language teachers design lessons, implement them, and assess student learning. Observation guides, interviews, documentation, and questionnaires were used to collect data, which were then analyzed to determine the instructional designs and strategies employed. The study was conducted at SDIT Mutiara Al-Madani Sungai Penuh. The findings revaled that: 1) The pedagogical competence of Arabic language teachers was generally good but still required enhancement, particularly their understanding of students, including various psychological aspects, learners’ needs and interests, talents, and individual differences; and 2) The management of Arabic language instruction related to pedagogical competence at the school did not fully meet the standards expected of professional teachers. This was evident from several aspects: first, instructional planning: some teachers did not design their own lesson plans; second, instructional implementation: teachers relied on a single method, primarily lecturing, rather than employing a variety of approaches; and third, evaluation of learning: teachers did not develop evaluation instruments or assessment questions adequately.